2014
DOI: 10.5194/bg-11-4651-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a plot-scale methane emission model using eddy covariance observations and footprint modelling

Abstract: Abstract. Most plot-scale methane emission models -of which many have been developed in the recent past -are validated using data collected with the closed-chamber technique. This method, however, suffers from a low spatial representativeness and a poor temporal resolution. Also, during a chamber-flux measurement the air within a chamber is separated from the ambient atmosphere, which negates the influence of wind on emissions.Additionally, some methane models are validated by upscaling fluxes based on the are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 64 publications
(73 reference statements)
0
41
0
Order By: Relevance
“…This is an important function for process-based models for simulating CH 4 emissions from wetlands with varying vegetation compositions. The high spatial variability of CH 4 emissions is often observed in boreal and arctic wetlands dominated by complex plant communities (Budishchev et al, 2014;Kutzbach et al, 2004;Morrissey and Livingston, 1992;Sebacher et al, 1986). Previous observations have shown that the CH 4 fluxes were lower at the moss site than the Carex site in the arctic tundra (Christensen, 1993).…”
Section: Importance Of Plant Community Composition In Ch 4 Simulationsmentioning
confidence: 98%
“…This is an important function for process-based models for simulating CH 4 emissions from wetlands with varying vegetation compositions. The high spatial variability of CH 4 emissions is often observed in boreal and arctic wetlands dominated by complex plant communities (Budishchev et al, 2014;Kutzbach et al, 2004;Morrissey and Livingston, 1992;Sebacher et al, 1986). Previous observations have shown that the CH 4 fluxes were lower at the moss site than the Carex site in the arctic tundra (Christensen, 1993).…”
Section: Importance Of Plant Community Composition In Ch 4 Simulationsmentioning
confidence: 98%
“…Several methods have been developed to upscale CH 4 fluxes, which often rely on the areal fraction of the vegetation community distribution around the EC tower [30]. The area-weighted average method uses the areal fraction of a vegetation community within a given area and multiplies it by CH 4 emissions derived from chamber measurements [33,81,82].…”
Section: Upscaling Ch 4 Emissionsmentioning
confidence: 99%
“…Eddy covariance (EC) and chambers are the most common methods to measure CH 4 fluxes in the field, and both give useful information [5,9,10]), but can also result in inaccurate emission predictions [29,30]. EC towers measure trace gas fluxes with a high temporal resolution across a footprint with radii of roughly 100-300 m for a tower 1-3 m tall [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the models also simulate the O 2 transport and the simulated O 2 concentrations affect the CH 4 processes. These models have been used in multiple studies (e.g., van Huissteden, 2009, 2011;Khvorostianov et al, 2008;Ringeval et al, 2011;Melton et al, 2013;Budishchev et al, 2014;Cresto Aleina et al, 2015;Grant et al, 2015), and some are referred to in the assessment report of the Intergovernmental Panel on Climate Change (IPCC; Ciais et al, 2013). These models have different approaches in simulating the production of CH 4 , ranging from separating distinct heterotrophic microbial communities (Grant and Roulet, 2002) to taking a constant fraction of the simulated heterotrophic soil respiration (Riley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%